Reading Godot - Gordon, Lois G. (Yale University Press, 2002)
"Waiting for Godot" has been acclaimed as the greatest play of the 20th century. It is also the most elusive: two lifelong friends sing, dance, laugh, weep, and question their fate on a road that descends from and goes nowhere. Throughout, they repeat their intention "Let's go", but this is inevitably followed by the direction "(They do not move.)". This is Beckett's poetic construct of the human condition. Lois Gordon, author of "The World of Samuel Beckett", has written this introduction to Beckett's great work for general readers, students and specialists. Critically and historically informed, it approaches the play scene by scene, exploring the text linguistically, philosophically, critically and biographically. Gordon argues that the play portrays more than the rational mind's search for self and worldly definition. It also dramatises Beckett's insights into human nature, into the emotional life that frequently invades rationality and liberates, victimises, or paralyzes the individual. Gordon shows that Beckett portrays humanity in conflict with mysterious forces both within and outside the self, and that he is an artist of the psychic distress born of relativism.